Agricultural mechanization in the dry zone of Myanmar - Filipski, Mateusz J.; Belton, Ben; van Asselt, Joanna (International Food Policy Research Institute, 2018)
This brief evaluates the extent of agricultural mechanization in four townships in Myanmar’s Dry Zone. It provides evidence that rapid mechanization is underway. Mechanical land preparation is now common-place, due to thriving machine rental markets, falling equip-ment prices, and better financing options. The mechanization of harvesting and threshing is also occurring but is concentrated in rice. These findings suggest that Dry Zone agriculture is at a technological crossroads.